2012
DOI: 10.3390/ijms131012519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genetically Engineered Stem Cells Expressing Cytosine Deaminase and Interferon-Beta or Carboxyl Esterase on the Growth of LNCaP Prostate Cancer Cells

Abstract: The risk of prostate cancer has been increasing in men by degrees. To develop a new prostate cancer therapy, we used a stem cell-derived gene directed prodrug enzyme system using human neural stem cells (hNSCs) that have a tumor-tropic effect. These hNSCs were transduced with the therapeutic genes for bacterial cytosine deaminase (CD), alone or in combination with the one encoding human interferon-beta (IFN-β) or rabbit carboxyl esterase (CE) to generate HB1.F3.CD, HB1.F3.CD.IFN-β, and HB1.F3.CE cells, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Among these, VEGF mRNA expression was significantly increased in Ishikawa cells. In a previous study, we confirmed that three genes encoding the uPA receptor (uPAR), VEGF receptor (VEGFR2), and SCF receptor (c-Kit) were strongly expressed compared to ones encoding SDF-1α receptor (CXCR4) and mCP-1 receptor (CCR2) in the stem cells (36). As an angiogenic factor, VEGF promotes the mobilization and recruitment of endothelial and hematopoietic stem cells into the neo-angiogenic site, thereby accelerating vasculogenesis and angiogenesis (37,38).…”
Section: Discussionmentioning
confidence: 53%
“…Among these, VEGF mRNA expression was significantly increased in Ishikawa cells. In a previous study, we confirmed that three genes encoding the uPA receptor (uPAR), VEGF receptor (VEGFR2), and SCF receptor (c-Kit) were strongly expressed compared to ones encoding SDF-1α receptor (CXCR4) and mCP-1 receptor (CCR2) in the stem cells (36). As an angiogenic factor, VEGF promotes the mobilization and recruitment of endothelial and hematopoietic stem cells into the neo-angiogenic site, thereby accelerating vasculogenesis and angiogenesis (37,38).…”
Section: Discussionmentioning
confidence: 53%
“…Two types of NSCs, HB1.F3.CD and HB1.F3.CD.IFN-β cells, may represent a novel approach for treating invasive tumors due to their inherent migratory and tumor-tropic properties as well as transgene expression (69)(70)(71). Since no effective treatments are available for most metastatic tumors, stem/progenitor cells expressing a suicide gene (CD) and cytokine (IFN-β) have the potential to improve the prognosis of patients with metastatic cancer (70).…”
Section: Other Origins Of Stem Cellsmentioning
confidence: 99%
“…Among these agents, genetic modification to overexpress interferon β was used in two preclinical trials (Table 1) [46, 52]. A significant increase in the natural kill cell activity was observed following IFN- β therapy correlating with the antitumor effect in prostate cancer model.…”
Section: Stem Cell Therapy Of Other Therapeutic Agentsmentioning
confidence: 99%